Some Middle School Students Want Behavior Commitment Devices (but Take-Up Does Not Affect Their Behavior) - Robinson, Carly D.; Pons, Gonzalo A.; Duckworth, Angela L.; Rogers, Todd (Frontiers in Psychology, 2018)
Commitment devices impose costs on one’s future self for failing to follow through on one’s intentions, offer no additional benefit to one’s future self for following through on the intention, and people voluntarily enroll in them. Enrollment in commitment devices reflects self-awareness that one may lack sufficient self-control to fulfill one’s intentions. There is little experimental research on whether school-age children possess the self-awareness necessary to enroll in a commitment device, despite evidence that children and young adolescents have many positive intentions that they fail to live up to, such as demonstrating improved school conduct or eating healthier. We report the first field experiment examining the demand for, and impact of, commitment devices among middle school students. We offered students a commitment device that imposed future costs for failing to improve in-school conduct. When presented with the opportunity to actively opt-in (default not enrolled), over one-third of students elected to enroll. When presented with the opportunity to actively opt-out (default enrolled), more than half elected to remain enrolled, showing that changing default options can increase commitment device enrollment. Despite demand for the self-control strategy, taking-up the commitment device did not affect student behavior. These findings have implications for youth-based behavioral interventions broadly, as well as those focused on eating behaviors.